Electronic and optical properties of hydrogen-terminated biphenylene nanoribbons: a first-principles study. Issue 1 (10th December 2021) - Shen, Hong; Yang, Riyi; Xie, Kun; Yu, Zhiyuan; Zheng, Yuxiang; Zhang, Rongjun; Chen, Liangyao; Wu, Bi-Ru; Su, Wan-Sheng; Wang, Songyou
Abstract : Pristine biphenylene exhibits metallic properties. However, for 1D nanoribbons, a direct–indirect transition occurs in the band gap as the width increases, transforming the nanoribbons to endow them with metallic characteristics at a certain width. Abstract : The electronic structures and optical properties of novel 2D biphenylene and hydrogen-terminated nanoribbons of different widths which are cut from a layer of biphenylene were explored via first-principles calculations. The findings of phonon computations demonstrate that such a biphenylene is dynamically stable and shows metallic properties. The crystal orbital Hamilton population analysis indicates that the tetra-ring local structure results in anisotropic mechanical properties. For 1D nanoribbons, their band gaps shrink, and a direct–indirect transition occurs in the band gap as the width increases, transforming the nanoribbon to endow them with metallic characteristics at a certain width. This is attributed to the weak coupling between the tetra-ring atoms, shrinking the direct band gap at the Y point in the Brillouin zone. Finally, the contribution of interband transitions to the dielectric function in 6-, 9-, and 12-armchair biphenylene nanoribbons (ABNRs) was identified. The lowest peak in the imaginary part of the dielectric function ε 2 spectrum was mainly a contribution of a Γ – Γ transition. As the width of ABNR increases, the transitions in the x direction become stronger while the transition strength in the y direction is not significantly altered. This investigation extends the understanding of the electronic and optical properties of 2D biphenylene and 1D nanoribbons, which will benefit the practical applications of these materials in optoelectronics and electronics.